Evaluation of secondary metabolites from commercially available Bacillus spp. probiotic products for their bioactivities - Nicolas, George Michael T (Animo Repository, 2024)
Spore-forming probiotics from Bacillus spp. enhance intestinal fortification, immune response, and eradicate gastrointestinal pathogens. The study isolated and identified six Bacillus spp. isolates from commercially available probiotic products TamiPro™, Jarrow Probiotics Duo™, and Youtheory Spore Probiotics™. 16s rRNA molecular identification of the probiotic isolates confirmed the identities of five (5) isolates indicated on the product literature, which were B. clausii MTCC 5980, B. subtilis MTCC 5981, B. subtilis DE111® and B. coagulans MTCC 5856. However, the B. clausii isolate in the TamiPro™ product literature was identified as B. cereus in two repeated assays. The antimicrobial activities of the secondary metabolites from the six (6) isolates in the 1) sterile culture supernatant, 2) ethyl acetate organic phase extract, 3) ethyl acetate aqueous phase extract, and 4) lyophilized ethyl acetate aqueous phase extract were tested on methicillin-resistant Staphylococcus aureus (MRSA) NBP 19B, MRSA NBP 39B, extended-spectrum beta-lactamase or ESβL (+) E. coli 168, ESβL (+) Klebsiella pneumoniae 245, and metallo-beta-lactamase or MβL (+) Acinetobacter baumannii ABL2 using the disc diffusion method. No zones of inhibition were observed in any of the organisms tested with any of the extracts. The lyophilized sterile culture supernatant of B. coagulans MTCC 5856 isolated from Youtheory Spore Probiotics™ was further tested for cytotoxicity on the human pancreatic cancer cell line BxPC-3 and the human normal liver cell line THLE-3 using the PrestoBlue™ resazurin assay. The results indicate that the B. coagulans MTCC 5856 secondary metabolites were significantly more cytotoxic (p < 0.05) in comparison to the pure compound ZeocinTM on the BxPC-3 cell line, indicating IC50 values of 228.3 μg/mL and 296.3 μg/mL, respectively. At the same time, the IC50 value for the normal cell line THLE-3 was 1444 μg/mL, which was significantly higher (p < 0.05) than that of ZeocinTM at 291.8 μg/mL, indicating non-cytotoxicity for lower concentrations. This suggests their potential use in the treatment of pancreatic cancer.